The Effectiveness of the Discovery Learning Model Assisted by Javalab and Hands-on Activities to Improve Students' Conceptual Understanding - Rochim, Achmad Nur; A Lende, Retno Sari Dewi; Nurohman, Sabar; Natadiwijaya, Ismail Fikri (Jurnal Pendidikan Sains Universitas Muhammadiyah Semarang, 2026)
Conceptual understanding is essential to science learning, yet Indonesian students still struggle, as evidenced by their low PISA 2022 science literacy score (383). Conventional teacher-centred instruction and limited laboratory facilities further limit opportunities to meaningfully explore and construct scientific concepts. This study aims to analyse the effectiveness of a discovery learning model integrated with JavaLab and hands-on activities in improving students’ conceptual understanding of work and energy. This Research used a pre-experimental one-group pretest-posttest involving 23 eighth-grade students at SMP Muhammadiyah 3 in Depok. Data were collected using a validated concept understanding test to assess reliability and analysed using descriptive statistics, normality tests, paired-samples t-tests, N-gain, and effect sizes. The findings showed that the mean score increased from 52.2 to 85.6, indicating a significant difference (Sig. = 0.000), with an N-gain of 0.69 (moderate). These results suggest that integrating virtual laboratories and hands-on activities within discovery learning can facilitate students’ conceptual understanding through exploration, verification, and concept generalisation. These findings suggest that teachers can adopt this approach to teach abstract concepts in schools with limited laboratory facilities. Future Research should use a quasi-experimental design with a control group and explore its application across broader topics and populations.